2017
DOI: 10.21608/ejh.2017.4662
|View full text |Cite
|
Sign up to set email alerts
|

Histological and immunohistochemical study on the potential toxicity of sliver nanoparticles on the structure of the spleen in adult male albino rats

Abstract: Introduction: Silver nanoparticles (AgNPs) remain one of the controversial research areas regarding their distribution, dissolution and their toxicity to biological systems. Aim of the work: To evaluate the potential toxicity of different doses of AgNPs on the spleen of adult Albino rats. Materials and Methods: Forty adult male albino rats were divided into two main groups; control group: included ten rats that received intraperitoneal saline solution, daily, and experimental group: included thirty rats that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The vacuolar degeneration observed in the parenchyma of the spleens treated with Olanzapine was consistent with other researchers, who suggested that silver nanoparticles induced autophagosomes containing cellular debris, disintegrated materials, lipid droplets, and changed intracellular homeostasis [26,27].…”
Section: Discussionsupporting
confidence: 90%
“…The vacuolar degeneration observed in the parenchyma of the spleens treated with Olanzapine was consistent with other researchers, who suggested that silver nanoparticles induced autophagosomes containing cellular debris, disintegrated materials, lipid droplets, and changed intracellular homeostasis [26,27].…”
Section: Discussionsupporting
confidence: 90%
“…These alterations included a reduction in the size of the white pulp follicles, as well as a depletion of lymphocytes, degeneration, and apoptosis. The spleen had structural changes that were consistent with an inflammatory response and oxidative stress after exposure to AgNPs [36]. An investigation by histopathology revealed congestion, bleeding, cellular degradation, apoptosis, and necrosis in the tissue of the liver and kidneys, in addition to lymphocytic depletion with growing visible macrophages in the spleen [37].…”
Section: Effects Of Silver Nanoparticles On Rat Spleenmentioning
confidence: 79%
“…Their potential for usage in biomedicine is greatly constrained by the utilization of expensive, unstable, and poisonous chemicals. Therefore, biological methods continue to be the best, including medicinal plant extracts, fungi, and prokaryotic bacteria which employed for the biological synthesis of AgNPs because it's time saving, cost-effective, and environmentally benign procedure [3].…”
Section: Introductionmentioning
confidence: 99%